1996
DOI: 10.1029/96gb02349
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation of carbon exchange fluxes in terrestrial ecosystems

Abstract: A global prognostic physiologically based model of the carbon budget in terrestrial ecosystems, the Frankfurt Biosphere Model (FBM), is applied to simulate the interannual variation of carbon exchange fluxes between the atmosphere and the terrestrial biosphere. The data on climatic forcing are based on Cramer and Leemans climate maps; the interannual variation is introduced according to records of temperature anomalies and precipitation anomalies for the period 1980 to 1993. The calculated net exchange flux be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 22 publications
7
102
2
Order By: Relevance
“…Years of anomalously poor tree growth at La Selva were years of peak inferred net emissions from the terrestrial tropics, and both of these records were significantly related to annual temperatures and El Niñ o. Such a relationship has been independently projected by three vegetation process models (Kindermann et al 1996;Gerard et al 1999;Ito & Oikawa 2000): in these simulations, temperature-driven variations in the NPP of tropical evergreen forests dominated the terrestrial component of the atmospheric CO 2 anomaly. Further empirical support for such a relationship between tropical NPP and temperature comes from three recent remote-sensing studies (Braswell et al 1997;Asner et al 2000;Los et al 2001): in all three analyses, satellite-derived measures of vegetation greenness (NDVI, normalized difference vegetation index) indicated reduced productivity in tropical ecosystems in warmer years.…”
Section: (Iii) Tree Mortality Peaks In Strong El Niño Eventsmentioning
confidence: 99%
“…Years of anomalously poor tree growth at La Selva were years of peak inferred net emissions from the terrestrial tropics, and both of these records were significantly related to annual temperatures and El Niñ o. Such a relationship has been independently projected by three vegetation process models (Kindermann et al 1996;Gerard et al 1999;Ito & Oikawa 2000): in these simulations, temperature-driven variations in the NPP of tropical evergreen forests dominated the terrestrial component of the atmospheric CO 2 anomaly. Further empirical support for such a relationship between tropical NPP and temperature comes from three recent remote-sensing studies (Braswell et al 1997;Asner et al 2000;Los et al 2001): in all three analyses, satellite-derived measures of vegetation greenness (NDVI, normalized difference vegetation index) indicated reduced productivity in tropical ecosystems in warmer years.…”
Section: (Iii) Tree Mortality Peaks In Strong El Niño Eventsmentioning
confidence: 99%
“…[5] ''Bottom-up'' studies used process-based biogeochemical models in climate models [Jones et al, 2001] or forced by climate fields to quantify regional IAV of carbon fluxes over land [Kindermann et al, 1996;Tian et al, 1998;Knorr, 2000;Gerard et al, 1999;Botta et al, 2002] and over the ocean [Le Quéré et al, 2003b;McKinley et al, 2004;Winguth et al, 1994]. Although those studies all agree in suggesting that the land IAV is larger than the ocean IAV, they may not attribute the IAV phenomenon to the same processes, and different models exhibit large discrepancies in the IAV regional signal [McGuire et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…[16] Biospheric model studies predict that plant respiration and soil decomposition are enhanced in ENSO years by above-average temperatures and precipitation, which leads to a reduction in net CO 2 uptake by the terrestrial biosphere [Kindermann et al, 1996;Ito and Oikawa, 2000]. A recent model calculation [Cao et al, 2003] on the interannual variations and trends in terrestrial carbon uptake caused by climate variability in China during the period of 1981 -1998 indicated that both temperature and precipitation reached the highest value in 1998, a record for the twentieth century, and resulted in the largest soil heterotrophic respiration (HR) in arid northwest China where WLG is located.…”
Section: Annual Means and Growth Ratesmentioning
confidence: 99%